Analysis of Systems and Applications For Registration of Independent Practical Health Service Facilities at the Karawang District Health Office in 2024 - Titin Wasiah; Fajar Saputra (Jurnal EduHealth, 2025)
The advancement of information technology within the health sector in Indonesia, including the administration and management of health facilities, is undergoing significant changes. The Karawang District Health Office, which is responsible for health facility management, has implemented a registration system for independent practicing health facilities. The study aimed to identify and evaluate the input, process, and output aspects of the existing registration system. The research method used a qualitative approach with in-depth interviews with relevant parties and direct observation of the health facility registration flow. The results showed that the existing registration system has been quite effective in improving administrative transparency and efficiency. In the input aspect, the digital-based registration system makes it easier for applicants to upload important documents such as Practice License (SIP) and Registration Certificate (STR). Technical constraints such as internet network problems and large file sizes are still an obstacle. On the process aspect, the registration flow involving several related parties such as the verification team and licensing manager has been running quite well, although there is a need to improve access rights management to protect sensitive data. On the output side, the system provides results in the form of registration numbers and status notifications that support monitoring and supervision by the Health Office and the Ministry of Health, but there are still potential errors in data input that need to be addressed. Suggestions The Karawang District Health Office made improvements to the technical infrastructure, as well as strengthening data management and verification to improve the quality and accuracy of the registration system such as training and socialization of registration demonstrations.